Persistently Low Maternal Knowledge on Congenital Hypothyroidism Screening in Newborns - Maretnawati Hura; Debi Novita Siregar; Elly Yuniarti; Melianta Debora Sianturi; Masdarniat Gea; Kristiana Solidarwati Zebua (FORIKES, 2026)
Congenital hypothyroidism is a congenital disorder caused by impaired thyroid gland function in newborns and may lead to growth retardation and permanent intellectual disability if not detected early. Congenital hypothyroidism screening is recommended by the World Health Organization and has been implemented nationally by the Ministry of Health of the Republic of Indonesia as part of newborn screening programs. However, screening coverage in several regions, including Nias Regency, has not yet reached the expected target. Maternal knowledge is considered one of the important factors influencing participation in this screening program. This study aimed to describe pregnant women’s knowledge regarding congenital hypothyroidism screening in newborns. This study employed a quantitative descriptive approach involving 21 pregnant women selected through accidental sampling. Data were collected using a structured questionnaire and analyzed using frequency distribution and percentage. The results showed that 28% of respondents had inadequate knowledge regarding screening indications, 24% had inadequate knowledge regarding screening procedures, and 33% had inadequate knowledge regarding screening benefits. Overall, 38% of respondents had inadequate knowledge regarding congenital hypothyroidism screening. These findings indicate that many pregnant women still have inadequate overall knowledge regarding congenital hypothyroidism screening in newborns.Keywords: congential hypothyroidism screening; knowledge; pregnant women